Meningkatkan Hasil Belajar Dalam Permainan Sepak Bola Dengan Menggunakan Model Pembelajaran Bermain Peran di SMA Al-Khairaat Labuha - Saiman, Rifaid; Sadek, Fajrin (Peneliti.net, 2026)
This study aims to improve the learning outcomes of dribbling skills in soccer games for Al-Khairaat Labuha High School students through the application of role-playing methods. The study used a Classroom Action Research (CAR) design implemented in two cycles. The subjects were 30 students of grade X, with assessment instruments covering affective, psychomotor, and cognitive aspects. Data were collected through observation, skills tests, and documentation, then analyzed using the percentage of learning completion technique. The results showed a significant increase from cycle I to cycle II. In cycle I, the average learning outcome of new students reached 67.23, with 19 students completing the course and 11 students not completing it. After improvements to the learning strategy in cycle II, the average learning outcome increased to 89.58, with 29 students completing the course and only 1 student not completing the course. This increase was seen in all aspects of the assessment: cognitive, psychomotor, and affective. Thus, it can be concluded that the application of the role-playing method is effective in improving the learning outcomes of dribbling students at Al-Khairaat Labuha High School. This method not only improves motor skills but also strengthens students' conceptual understanding and sportsmanship.